Indeks Toleran dan Evaluasi Karakter Seleksi Jagung Hibrida terhadap Pemupukan N Rendah - Herawati, Herawati; Efendi, Roy; Azrai, M. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
The hybrid maize that tolerant low N is one of technology to resolve of N limitation for growth and production of maize. Therefore, tolerance index analysis and evaluation of the hybrid maize’s character which tolerant low N need to be done. This study aimed to know the genotype of hybrid maize that are tolerant low N and characters that can be used as selection indicator to low N. Research conducted at the Experimental Farm of ICERI, Maros from June until November 2014. This research was arranged in split plot design with three replication. The main plot was nitrogen fertilizer which consists three levels ie 0 kg N/ha, 100 kg N/ha (low N fertilization dosage) dan 200 kg N/ha (dosage of normal N fertilization). The subplot were 56 hybrid maize genotypes. There are four check varieties ie P-27, NK-33, Bisi-2, and Bima-3. The results showed that HLN 32 had the highest grain yield on low N (10,02t/ha). Genotypes of hybrid maize that tolerant low N were HLN03, HLN17, HLN18, HLN24, HLN25, HLN32, HLN35, HLN39, HLN46, and HLN47. The plant height, ear height position, steam diameter, leaf width, leaf area, age of male flowering, age of female flowering, leaf chlorophyll at age 80 after planting, leaf senescence, percentage of normal cobs, percentage of abnormal cobs, ear height, ear diameter, number of kernels per row, number of kernels per cob, and shelling percentage. Characters that have direct influence to grain yield were shelling percentage, percentage of abnormal cobs, ear height, ear diameter, and leaf area.